Analytical Variables Affecting Analysis of F2-Isoprostanes and F4-Neuroprostanes in Human Cerebrospinal Fluid by Gas Chromatography/Mass Spectrometry. (10th July 2013) - Yen, Hsiu-Chuan; Wei, Hsing-Ju; Chen, Ting-Wei
Abstract : F2 -isoprostanes (F2 -IsoPs) are a gold marker of lipid peroxidation in vivo, whereas F4 -neuroprostanes (F4 -NPs) measured in cerebrospinal fluid (CSF) or brain tissue selectively indicate neuronal oxidative damage. Gas chromatography/negative-ion chemical-ionization mass spectrometry (GC/NICI-MS) is the most sensitive and robust method for quantifying these compounds, which is essential for CSF samples because abundance of these compounds in CSF is very low. The present study revealed potential interferences on the analysis of F2 -IsoPs and F4 -NPs in CSF by GC/NICI-MS due to the use of improper analytical methods that have been employed in the literature. First, simultaneous quantification of F2 -IsoPs and F4 -NPs in CSF samples processed for F4 -NPs analysis could cause poor chromatographic separation and falsely higher F2 -IsoPs values for CSF samples with high levels of F2 -IsoPs and F4 -NPs. Second, retention of unknown substances in GC columns from CSF samples during F4 -NPs analysis and from plasma samples during F2 -IsoPs analysis might interfere with F4 -NPs analysis of subsequent runs, which could be solved by holding columns at a high temperature for a period of time after data acquisition. Therefore, these special issues should be taken into consideration when performing analysis of F2 -IsoPs and F4 -NPs in CSF to avoid misleading results.